Enhancing the material performance of chloroprene rubber (CR) by strategic incorporation of zirconia. Issue 5 (7th February 2022) - Ambilkar, Shubham C.; Dhakar, Gopal Lal; Kapgate, Bharat P.; Das, Amit; Hait, Sakrit; Gedam, R. S.; Kasilingam, Rajkumar; Das, Chayan
Abstract : Superior reinforcement effect along with other useful composite properties are offered by uniformly dispersed in situ incorporated zirconia in chloroprene rubber matrix. Abstract : Chloroprene rubber (CR) composites, embedded with well dispersed zirconia within the matrix, are produced that combine the superior reinforcement of zirconia with the other useful composite properties. The in situ incorporated zirconia offers an outstanding reinforcement effect in comparison to externally filled zirconia at the same filler content. The modulus at 100% strain becomes four times higher for a 20 phr in situ filled zirconia composite, with respect to an unfilled compound while the tensile strength becomes three times higher. A notable improvement in thermal stability is exhibited by an increase in the onset temperature and maximum degradation temperature by ca. 30 °C and 20 °C respectively upon in situ zirconia incorporation. The use of two selected organosilanes results in further improvement in composite properties. A study on the dielectric properties of the composites seems very encouraging. The zirconia filled composites also respond very well to a series of testing viz. resistance to oil, aging and abrasion exhibiting their suitability for practical application.